2016
DOI: 10.1111/ane.12723
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients with anti-NMDA receptor encephalitis

Abstract: GCS score ≤8 at admission, number of complications, and admission to an intensive care unit are predictors of death. Management of complications may improve the prognosis of anti-NMDAR encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 24 publications
7
69
5
Order By: Relevance
“…In addition, a more aggressive treatment approach and prevention of detrimental courses by proactive ICU admission in more recent years might have played a role. Moreover, we could not confirm the observations from mostly larger but historical patient series which disclosed an association of age, ICU admission, and poor functional outcome ( 4 , 8 , 13 , 26 ). Thus, whether increased earlier diagnosis, improved understanding, and an altered treatment approach are responsible for our observation, needs to be confirmed in future independent studies.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In addition, a more aggressive treatment approach and prevention of detrimental courses by proactive ICU admission in more recent years might have played a role. Moreover, we could not confirm the observations from mostly larger but historical patient series which disclosed an association of age, ICU admission, and poor functional outcome ( 4 , 8 , 13 , 26 ). Thus, whether increased earlier diagnosis, improved understanding, and an altered treatment approach are responsible for our observation, needs to be confirmed in future independent studies.…”
Section: Discussioncontrasting
confidence: 83%
“…Timely diagnosis and initiation of immunotherapy is a key prognostic factor ( 8 , 11 ). Development of life-threatening complications requiring ICU admission has been linked to a prolonged hospital stay and lower likelihood of favorable outcome from AE ( 12 , 13 ). Unraveling risk factors for the development of critical illness in patients with AE could help to improve morbidity and mortality of this condition by allowing for early monitoring and aggressive supportive care.…”
Section: Introductionmentioning
confidence: 99%
“…Our sample showed that the non‐catatonic group had a higher mortality, mainly related to treatment‐resistant status epilepticus. In other studies, risk factors such as status epilepticus, admission to an intensive care unit, Glasgow Coma Scale score ≤ 8, and delay of immunomodulatory treatment have been associated to a poorer prognosis in terms of morbidity and mortality …”
Section: Discussionmentioning
confidence: 95%
“…In other studies, risk factors such as status epilepticus, admission to an intensive care unit, Glasgow Coma Scale score ≤ 8, and delay of immunomodulatory treatment have been associated to a poorer prognosis in terms of morbidity and mortality. 1,22 In our sample, symptomatic treatment of severe catatonic excitement was required for the safe use of plasma exchange. Rather than attempting to treat catatonia itself expecting its remission, the goal of these symptomatic treatments was to keep patients as safe as possible (using the safest psychotropics as needed, including lorazepam) while the underlying condition was treated with immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…The relapse rate may be associated with duration of followup. The fatality rate of anti-NMDAR encephalitis ranges from 0-12.5% [10,28,29,20,16,14,15] (See Additional le 1: Table S1). While it was 1.8% in current study, that was similar to studies from other region of China [20,16,14,15], which ranged from 0.0-2.3% (See Additional le 1: Table S1), being relatively low.…”
Section: Discussionmentioning
confidence: 99%